EFL Students’ Perception of Mobile Technology-Mediated Task-Based Language Teaching - Siti Muhibbatul Maufuroh; Elih Sutisna Yanto; Totoh Tauhidin Abas (JELLT (Journal of English Language and Language Teaching), 2022)
Technology in education makes it easy for us to find various sources of knowledge quickly and can be done anytime and anywhere. However, teachers must have appropriate methods to implement during teachings, such as providing media, teaching techniques, or learning strategies. This encourages researchers' interest in utilizing the Hello English application in the classroom as mobile technology students can use to learn English. This study aims to determine EFL students' perceptions of the use of mobile technology in task-based language teaching. A case study was used to conduct the research in a qualitative way. The participant in this study is three students from junior high school in Karawang. Data collection in this study used student observations, interviews, and documentation. The data analysis uses the thematic analysis of Braun & Clarke (2006); there are six steps: get to know the data, produce initial codes, search for themes, review themes, define and name themes, and write the report. The results show that EFL students' perceptions of mobile technology in task-based language teaching received a positive response. Also, affect students' learning, specifically in the context of vocabulary learning, which is the primary issue in English classes.